Biopolitics beyond Foucault. A Critique of Agamben’s Analysis of the Pandemic - Antoniol, Valentina (Soft Power, 2024)
The outbreak of the Covid-19 pandemic has profoundly changed our image of the world and it is precisely with this new image that — regardless of our different political, legal, economic, social and, not least, health status or condition — we are all called to grapple. In other words, we cannot avoid to measure ourselves against this unprecedented event that has forced a radical reorganization of our lives. Yet, if it is true that such a condition leads us directly to experience the dramatic character of the present situation, it is equally certain that each of us — precisely in relation to its specificity — lives a particular drama in an absolutely unique way. Taking up — mutatis mutandis — a famous passage from Marx’s Introduction to the Grundrisse, we could say that: «Hunger is hunger, but the hunger gratified by cooked meat eaten with a knife and fork is a different hunger from that which bolts down raw meat with the aid of hand, nail and tooth» (Marx, 1993, p. 92)